Experimental evidence of subtle victim blame in the absence of explicit blame. - Carolyn L Hafer; Alicia N Rubel; Caroline E Drolet (PLoS ONE)
We argue that people will often eschew explicit victim blame (e.g., claiming that "X is to blame") because it is counternormative and socially undesirable, yet they might still engage in subtle victim blame by attributing victims' suffering to behaviors the victims can control (i.e., "high control causes"). We found support for this argument in three online studies with US residents. In Studies 1 and 2, participants viewed a victim posing either a high threat to the need to believe in a just world, which should heighten the motivation to engage in victim blame, or a low threat. They then rated explicit blame items and attributions for the victim's suffering. Explicit blame was low overall and not influenced by victim threat. However, participants attributed the high threat victim's suffering, more than the low threat victim's suffering, to high control causes, thus showing a subtle blame effect. In Study 2, explicit blame and subtle blame were less strongly associated (in the high threat condition) for individuals high in socially desirable responding. These results are consistent with our argument that explicit and subtle blame diverge in part due to social desirability concerns. In Study 3, most participants believed others viewed the explicit blame items, but not the attribution items, as assessing blame. Thus, attributions to high control causes can be seen as "subtle" in the sense that people believe others will view such statements as reflecting constructs other than blame. Our studies suggest a way of responding to innocent victims that could be particularly relevant in a modern context, given increasing social undesirability of various negative responses to disadvantaged and victimized individuals.